(untitled) (Proceedings of International Conference on Special Education, 2015)
This paper deals with the experiences of blind students in inclusive tertiary classes. Following the qualitative method, this paper investigated the phenomenon of students of the School of Teacher Education in Saint Louis University, Baguio City, Philippines. Semi-structured interviews were conducted to gather data from four (4) blind students. The data gathering was triangulated through interviews with the close friends of the blind students who are with them in their various classes. The interviews were conducted from forty (40) minutes to one (1) hour at the most convenient time and place of the key informants. The use of cool and warm analysis helped bring out the experiences of the research participants. Interestingly, two (2) main themes with three (3) sub-themes emerged from the study, namely: positive experiences - making me feel comfortable, making me feel motivated, and making me feel important; and negative experiences - making me feel discriminated, making me feel embarrassed, and making me feel worried.